THE FIGURE OF T.G. SHEVCHENKO IN THE PEDAGOGICAL MAGAZINE "SVITLO" (Kyiv, 1910-1914). - Зайченко, І.В. (Modern engineering and innovative technologies, 2024)
The article presents the materials of the Ukrainian-language pedagogical magazine "Svitlo" (Kyiv, 1910-1914), dedicated to the figure of T.G. Shevchenko. The materials of S. Efremov, S. Volokh, Ya. Zelenkevych (Chepigy), D. Pisochynets, S. Rusova, S. Cher